Study on the impact of intermittent heating control strategy system on greenhouse thermal environment - Mingzhi Zhao; Yingjie Liu; Zheng Han; Chun Chang; Daorina Bao; Rasakhodzhaev Bakhramzhan Sabirovich; Akhadou Jobir (Case Studies in Thermal Engineering)
The heating imbalance in solar-powered heating greenhouses (SHG) severely constrains both energy supply efficiency and crop yield. This study proposes the principle of Thermal Intermittent Heating (TIH), unveiling the differentiated regulatory mechanisms by which the duty cycle (∅) governs thermal dynamics in both aerial greenhouse environments and subsurface soil layers. Under the greenhouse thermal environment conditions, the operational mode with ∅ = 0.67 (control scheme (2,1)) demonstrates optimal thermal stratification adaptation through an 8-h heating/4-h intermittent cycle. This configuration achieved the highest Comprehensive Energy Energy Efficiency Index (COP) of 88.7 % in the fourth layer (group maximum), along with minimal thermal fluctuations indicated by σT (2.82 °C) and CV (11.12 %). The strategy effectively compensates for thermal dissipation in upper zones caused by buoyant airflow (48 % elevation in mean temperature), while preventing excessive top-layer overheating observed in continuous heating (∅ = 1) scenarios, which exhibited 128 % surge in σT. Within the soil layer (0.1–0.2m depth), this ∅ value synchronously optimizes thermal penetration intensity and stability: The first-layer COP reached 182.39 (T‾ = 19.72 °C) with σT merely 1.85 °C, where heating duration precisely matched the soil's thermal diffusion period (6–8 h). Whereas ∅ = 1 induced 197 % surge in soil σT (5.51 °C vs. optimal condition), and ∅ = 0.13 resulted in 22.6 % reduction in deep-layer temperature mean. The study demonstrates COP's capacity to quantify heterogeneous thermal responses across media, revealing that moderate ∅ = 0.67 regulates thermal inertia to achieve multi-objective synergy in ''energy consumption-uniformity-thermal penetration''. This establishes a thermodynamic analysis framework for hierarchical heating system optimization.